MAINTAINING THE HEALTH OF STUDENTS AS A NECESSARY CONDITION FOR THE FORMATION OF THE EDUCATIONAL ENVIRONMENT - Нелли Борисовна Пястолова (Физическая культура. Спорт. Туризм. Двигательная рекреация, 2020)
The theme of “Preservation and improvement of health” currently is very important and topical, so the problem of supporting the health of students in higher education institutions on the example of the Chelyabinsk state University is reviewed. The purpose and objectives of the study. Consider the preservation of health as a necessary condition for the formation of the educational environment of students in the Chelyabinsk state University (CSU). In accordance with the purpose, the following objectives of the study were defined: — to study and analyze the degree of development of the health protection program in CSU; — to reveal the structure and content of the concept of “health protection”; — to offer recommendations for improving the health of the educational environment in CSU; — to develop the program “Health care in the CSU”. The main goal of the program “health Care in CSU” is to preserve and strengthen the health of students, teachers and employees of CSU by creating conditions for physical, psychological, social and spiritual comfort. It is recommended to solve this problem by improving the quality of health preserving education.